PROFIL PERKEMBANGAN SOSIAL ANAK KELOMPOK B DALAM BERMAIN PERAN - Dewi, Mutiara Sari (Thufuli, 2019)
Social development is one aspect of development that must be stimulated early. Based on observational data made regarding the daily lives of group B children at Ar-Rahman Kindergarten, Jombang, it appears that children are better able to socialize with peers or with people who are older than children from other institutions. One form of stimulus for social development in kindergarten, specifically for children aged 5-6 years (group B) kindergarten can be done through role playing.This research is a research with descriptive quantitative research. Data analysis techniques use descriptive with percentage. The study was conducted in group B, TK Ar-Rahman, Jombang Regency with a sample of 56 children.Based on the results of these studies, it can be concluded that the profile of social development of child B, TK Ar-Rahman Jombang, is in good category (3) on indicators: 1) able to support with friends; 2) purchase at game level; and 3) able to ask and answer questions. Each indicator, category (3) has the highest percentage. A total of 32 children (57.1%) worked together in role playing activities to become family members with only 1 (one) command. 34 children (60.7%) were able to obey 3 (two) rules of the game in role playing. 28 children (50%) were able to ask and answer questions while playing roles.